El control de los sesgos cognitivos en el contexto jurídico procesal: medidas preventivas y correctivas y deberes de responsabilidad epistémica - Bustamante Requena, José Francisco (Pontificia Universidad Católica del Perú, 2024)
This work aims to critically reflect on the problematic relationship between cognitive biases and the procedural legal context, as well as the need to adopt measures to avoid their serious repercussions on judicial decisions. For this purpose, focuses on generality of the studies on the part of previous attempts at improvement are found to be problematic, which are mainly oriented towards the identification of possible actions that should be adopted on a case-by-case basis, in many cases their reasonableness and, above all, being discussed. Its relevance in the task of mitigating or reducing cognitive biases. To overcome these obstacles, two aspects are taken into consideration: the procedures and practices of judicial processes and the preservation of the guarantee and duty of impartiality and how the design of the processes and their dynamics —not always oriented to maximizing impartiality—allow the obtaining decisions compatible with said guarantee. Finally, an intervention scheme is outlined that brings together, on the one hand, the analysis of legal norms and rules (and their impact) on the modification and correction of some legal procedures and practices and, on the other, is complemented by a structured set of duties of epistemic responsibility.

El presente trabajo pretende reflexionar críticamente la problemática relación entre los sesgos cognitivos y el contexto jurídico procesal, del mismo modo la necesidad de adoptar medidas para evitar sus graves repercusiones sobre las decisiones judiciales. Para ese propósito, se enfoca en la generalidad de los estudios e intentos de superación previos, los que principalmente se orientan a la identificación de posibles acciones que se deberían adoptar caso por caso, siendo en muchos casos discutida su razonabilidad y sobre todo su relevancia en la tarea de mitigación o reducción de sesgos cognitivos. Para superar estos obstáculos se toman en consideración dos aspectos: los procedimientos y prácticas de los procesos judiciales y la preservación de la garantía y deber de imparcialidad y cómo el diseño de los procesos judiciales y su dinámica —no siempre orientados a maximizar la imparcialidad— permiten la obtención de decisiones compatibles con dicha garantía. Finalmente, se esboza un esquema de intervención que agrupa, por un lado, el análisis de las normas y reglas jurídicas (y su incidencia) en la modificación y corrección de algunos procedimientos y prácticas jurídicas y, de otro, se complementa por un conjunto estructurado de deberes de responsabilidad epistémica.
The control of cognitive bias in the procedural legal context: preventive and corrective measures and obligation of epistemic responsability
Keywords: Heuristic; Bias; Hipótesis; Standar; Debiasing; Epistemic responsability; Heurística; Sesgo; Hipótesis; Estándar; Desprejuiciar; Responsabilidad epistémica; https://purl.org/pe-repo/ocde/ford#5.05.00